Algoritma Levenshtein Distance sebagai Solusi Efisiensi Pencarian pada Training Registration System - Iqbal Faris Akbar; Mugiarso; Khairunnisa Fadhilla Ramdhania; Rasim (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2024)
The training registration process at Company XYZ faced several challenges, including the use of physical documents, slow file submission, non-standardized document numbering, and inefficient file storage. This research aimed to develop a web-based application called